The homing place : - Bryant, Rachel (Wilfrid Laurier University Press, 2017)
Can literary criticism help transform entrenched Settler Canadian understandings of history and place? How are nationalist historiographies, insular regionalisms, established knowledge systems, state borders, and narrow definitions continuing to hinder the transfer of information across epistemological divides in the twenty-first century? What might nation-to-nation literary relations look like? Through readings of a wide range of northeastern texts - including Puritan captivity narratives, Wabanaki wampum belts, and contemporary Innu poetry - Rachel Bryant explores how colonized and Indigenous environments occupy the same given geographical coordinates even while existing in distinct epistemological worlds. Her analyses call for a vital and unprecedented process of listening to the stories that Indigenous peoples have been telling about this continent for centuries. At the same time, she performs this process herself, creating a model for listening and for incorporating those stories throughout. This commitment to listening is analogous to homing - the sophisticated skill that turtles, insects, lobsters, birds, and countless other beings use to return to sites of familiarity. Bryant adopts the homing process as a reading strategy that continuously seeks to transcend the distortions and distractions that were intentionally built into Settler Canadian culture across centuries.
10.51644/9781771122887
Keywords: .; American studies.; Canadian studies.; Indigenous literacies.; Indigenous studies.; atlantic world.; border studies.; colonial northeast.; eastern Canada.; hemispheric studies.; literary history.; non-alphabetic literature.; northeastern North America.; reconciliation.; settler colonial studies.; transatlantic.; what is an early American.; what is literature.; Canadian literature